2015
DOI: 10.1111/acer.12703
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Trial of Prazosin, an Alpha‐1 Adrenergic Antagonist, for Comorbid Alcohol Dependence and Posttraumatic Stress Disorder

Abstract: Background Posttraumatic Stress Disorder (PTSD) and alcohol dependence (AD) commonly co-occur and are associated with greater symptom severity and costs than either disorder alone. No pharmacologic interventions have been found to decrease both alcohol use and PTSD symptom severity relative to matched placebo. Prazosin, an alpha-1 adrenoreceptor antagonist, has demonstrated efficacy reducing PTSD and AD symptoms among individuals with one or the other disorder and may be useful in addressing comorbid PTSD/AD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 48 publications
5
67
1
Order By: Relevance
“…In one outpatient, DBPC pilot study of 17 men with alcohol dependence, prazosin dramatically reduced the number of drinks consumed by 88% and the number of drinking days by 84% during the final 3 weeks of the 6-week study (Simpson et al, 2009). This finding was confirmed in a second outpatient pilot study by the same group that involved 20 men and women with alcohol dependence and PTSD, though 6 in the prazosin group required dose reductions for side effects (Simpson et al, 2015). However, a more extensive, outpatient, DBPC trial of 96 veterans with alcohol dependence and PTSD found no significant effect of prazosin over placebo on drinking measures during 13 weeks of treatment (Petrakis et al, 2016).…”
Section: Resultsmentioning
confidence: 74%
“…In one outpatient, DBPC pilot study of 17 men with alcohol dependence, prazosin dramatically reduced the number of drinks consumed by 88% and the number of drinking days by 84% during the final 3 weeks of the 6-week study (Simpson et al, 2009). This finding was confirmed in a second outpatient pilot study by the same group that involved 20 men and women with alcohol dependence and PTSD, though 6 in the prazosin group required dose reductions for side effects (Simpson et al, 2015). However, a more extensive, outpatient, DBPC trial of 96 veterans with alcohol dependence and PTSD found no significant effect of prazosin over placebo on drinking measures during 13 weeks of treatment (Petrakis et al, 2016).…”
Section: Resultsmentioning
confidence: 74%
“…Several RCTs with varying sample sizes of veterans and civilians demonstrate safety, tolerability and efficacy of prazosin to reduce nightmares, sleep impairment, and overall PTSD symptom severity [1,18,5153,59,68], as well as AUD severity [59,60]. However, the largest RCT to date examining prazosin in the treatment of PTSD ( N = 304) [49] resulted in null findings.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have examined the use of prazosin, an alpha-1 noradrenergic blocker approved by the U.S. Food and Drug Administration (FDA) for hypertension and benign prostatic hyperplasia, in the treatment of PTSD, AUD and comorbid AUD/PTSD. The findings have been mixed with some studies showing significant reduction in AUD symptoms [15,59,60] and reduction in PTSD symptoms, particularly nightmares, sleep disruption and daytime hyperarousal symptoms [18,50,52], while other studies find no significant differences in prazosin vs. placebo for AUD or PTSD symptoms [41,49]. Several studies suggest that pre-treatment blood pressure may represent a biomarker to help identify who will respond favorably to prazosin, or potentially other alpha-1 blockers [48,74].…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that prazosin is effective especially in the presence of post-traumatic stress disorder comorbidity (140,141).…”
Section: Pharmacological Treatment Options For Alcohol Use Disordermentioning
confidence: 99%